2010
DOI: 10.2217/whe.10.67
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Stimulation: Is There a Long-Term Risk for Ovarian, Breast and Endometrial Cancer?

Abstract: Adverse effects have been related to infertility treatments. Infertility in general, and female infertility in particular, is a well established risk factor for cancer development, especially ovarian, breast and endometrial cancer. This article addresses the possible association between infertility and cancer development, with an emphasis on the influence of infertility treatments, through a meticulous search of the literature published thus far. While results regarding the possible association of infertility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 82 publications
(92 reference statements)
1
10
0
Order By: Relevance
“…A number of authors [14,[21][22][23] have suggested that this apparent increase in risk may not be causal, but rather due to surveillance bias. Surveillance bias is a case of "the more you look, the more you find"; the premise being that women who have IVF will be examined more often than women who do not, providing more opportunities for detection.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors [14,[21][22][23] have suggested that this apparent increase in risk may not be causal, but rather due to surveillance bias. Surveillance bias is a case of "the more you look, the more you find"; the premise being that women who have IVF will be examined more often than women who do not, providing more opportunities for detection.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of mice pre-implantation embryo development provides a rationale to analyze current results of ART and PGD procedures (such as the increased risk for alterations in imprinting and other defects already observed in clinical and epidemiological studies), in the light of their potential molecular mechanisms and epigenetic processes. Moreover, the genetic and epigenetic processes already known to be involved in these events suggest that following these techniques not only mothers [Calderon-Margalit et al, 2009;Lerner-Geva et al, 2010] but also their apparently normal newborn infants might be carrying lifetime health risks.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are publications, which have not found a relation between infertility treatments and any cancer development (Potashnik et al, 1999, Doyle et al, 2002Dor et al, 2002;Lerner-Geva et al, 2010;Brinton et al, 2004). For example, a case-control study (1380 pairs) showed no risk for IVF treatment even among women who carry mutations in breast cancer susceptibility gene 1 (BRCA1) or BRCA2 gene (Kotsopoulos et al, 2008).…”
Section: The Risk For Cancer Development After Ivf Treatmentmentioning
confidence: 99%